2014
DOI: 10.1093/forestry/cpu044
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of productivity in pine and oak forests in northern Portugal using Biome-BGC

Abstract: Studies about the productivity of forest ecosystems help to quantify sequestered carbon and provide data that are used in forest management. Forests in northern Portugal are an important economic resource, but their productivity in scenarios of future climate change is not yet well understood. The objectives of this study were to evaluate and compare simulated net primary production (NPP) and NPP based on measured data of two tree species located in the Vila Real district forests, pine (Pinus pinaster Aiton) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Combining the validations in previous and current studies, this study suggested that the Biome-BGC model was suitable for estimating annual NPP and transpiration of P. crassifolia forest under current climate and CO 2 concentration conditions. Thus, the validation exercise provided a level of confidence in the model capability to project the impacts of climate change and changing atmospheric CO 2 concentrations on NPP and transpiration of P. crassifolia forest at each site under future climatic conditions and CO 2 concentration, as suggested by Nunes et al [8] and Su et al [7].…”
Section: Model Validationmentioning
confidence: 94%
See 3 more Smart Citations
“…Combining the validations in previous and current studies, this study suggested that the Biome-BGC model was suitable for estimating annual NPP and transpiration of P. crassifolia forest under current climate and CO 2 concentration conditions. Thus, the validation exercise provided a level of confidence in the model capability to project the impacts of climate change and changing atmospheric CO 2 concentrations on NPP and transpiration of P. crassifolia forest at each site under future climatic conditions and CO 2 concentration, as suggested by Nunes et al [8] and Su et al [7].…”
Section: Model Validationmentioning
confidence: 94%
“…Moreover, utilization of the model for predicting flux changes under future climate and atmospheric CO 2 concentration scenarios has been described [7,8]. First, model outputs under current climate and atmospheric CO 2 concentration conditions should be validated using the field-based data.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few cases have not shown any trends or have shown a decrease in productivity with extreme growth limitations (Lawrence et al 2005;Lucht et al 2002). Nunes et al (2015) stated that the NPP of temperate Mediterranean forests (Pinus pinaster Aiton and Quercus pyrenaica Willd. forests) in northern Portugal will increase with a CO 2 increase, whereas higher temperatures and lower soil moisture will result in an NPP decrease in the future.…”
Section: Introductionmentioning
confidence: 99%